Migrant Workers and Changing Work-place Regimes in Contemporary Agricultural Production in Canada - Preibisch, Kerry (The International Journal of Sociology of Agriculture and Food, 2012)
Contemporary processes of globalization have had significant implications for food systems around the world. The adoption of neo-liberal policies on a global scale, changing systems of governance in supply chains, and the development of new technologies have transformed how food is produced and consumed. Although the implications of these changes for the labour sustaining agri-food systems have received scant attention in the literature, research suggests they are profound. In this article, I seek to further our knowledge of how these processes are unfolding in a high income country context through a focus on Canada, examining in particular how changes to immigration policy have rendered work in Northern agri-food industries more precarious. In so doing, I seek to contribute to theoretical debates on the role of the state in regulating work-place regimes and managing capitalist accumulation in agriculture.